Antihyperglicemic effect of Musa paradisiaca extract in vivo - Noor Hujjatusnaini; Ridha Nirmalasari (Medisains)
Background: Musa paradisiaca hasÂ  been widely studied for its antihyperglycemic effects, showing potential as an alternative natural remedy for diabetes. However, variability in genetic factors, environmental conditions, and geographical origins may influence its bioactive compound composition and efficacy. Thus, further validation through controlled studies is required to ensure consistent therapeutic effects.